Texts and traditions : essays in honour of J. Keith Elliot - Elliott, J. K. (New Testament Tools, Studies and Documents, 2014)
The methodology of New Testament textual criticism, the critical evaluation of readings, and the history and texts of early Christianity is the focus of the influential work of J. K. Elliott. Texts and Traditions offers eighteen essays in his honour. The essays, by colleagues and students from his long career, reflect Elliott's wide interest and impact. From questions of the purpose and practice of textual criticism, to detailed assessment of New Testament literature and the readings of its manuscripts, to provocative studies of the reception of Jesus and the New Testament in the second century, this volume will be of value to those studying the New Testament and Early Christianity.